APPLICATION OF ANTIPLATELET AND ANGIOPROTECTIVE THERAPY IN PATIENTS WITH PLACENTAL INSUFFICIENCY DEVELOPMENT RISK FACTORS - A. V. Vorobiev (Медицинский совет, 2016)
The article describes the basic principles of correction and prevention of subclinical forms of placental insufficiency in patients with anamnestic  risk factors for the development of this pathology. Pathogenetic substantiation of administration of antiplatelet and angioprotective therapy during pregnancy in risk group patients is provided. It is given to discuss the possibilities of early detection of risk factors and prevention of clinical manifestations.